Discrete thermal analysis of a marine reboiler under transcritical pressure conditions - Kaya, Ibrahim; Ust, Yasin (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
In response to the growing emphasis on greenhouse gas reduction, energy efficiency, and the decarbonization objectives of the International Maritime Organization, Transcritical Organic Rankine cycles have emerged as a promising technology for waste heat recovery at vessels. However, conducting thermal analyses of the heat exchangers operating under transcritical pressure conditions remains challenging due to the sharp variations in thermo-physical properties near the critical point. Consequently, conventional analysis methods, such as the effectiveness-number of transfer units (epsilon-NTU) method, often exhibit numerical instability or fail to converge under transcritical conditions. To overcome this limitation, the Discrete Sub-Heat Exchanger (DSHE) method was developed, wherein the heat exchanger is discretized into multiple sub-heat exchanger pairs with locally constant fluid properties at defined area condition. The method was implemented for the thermal analysis of a marine reboiler integrated into a waste heat recovery system operated by the exhaust gases of a 1980 kW turbocharged Tier-II marine diesel engine. Comparative simulations revealed that the epsilon-NTU method fails to converge at specific transcritical pressure and mass flow rate ranges, whereas the DSHE approach provides stable and consistent solutions. At higher pressures and mass flow rates, the deviation between outlet temperatures predicted by both methods decreases from approximately 20% to below 2%. Sensitivity analyses verified the numerical stability of the DSHE modelling, achieving convergence with residuals on the order of 10-5-10-6 beyond 1000 discrete elements. Overall, the DSHE method demonstrates a reliable and consistent tool for the thermal analysis of heat exchangers under transcritical pressure conditions, offering a robust approach for future studies involving two-phase or complex flow configurations with algorithm acceleration methods.
Keywords: Thermal analysis in the Transcritical flow; Discrete thermal analysis of a reboiler; Waste heat recovery at vessels; ECONOMIC PERFORMANCES OPTIMIZATION; ORGANIC RANKINE CYCLES; HEAT-EXCHANGER; WASTE HEAT; SYSTEM; ENGINE; Thermodynamics; Energy & Fuels; Engineering; Mechanics